The Influence of Career Development, Job Satisfaction, and Organizational Culture on Employee Loyalty - Bagus Pramudita; Joko Suyono; Damarsari Ratnasahara Elisabeth (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to determine the effect of career development, job satisfaction, and organizational culture partially and simultaneously on employee loyalty of Logistics Company in Surabaya in Surabaya. This type of research is quantitative, where the researcher distributes questionnaires as a medium for data collection and then processes them into questionnaire interval data which is then processed using SPSS 25. The population and sample of this study amounted to 74 employees of a Logistics Company in Surabaya. Partial hypothesis test results Partial career development positive and significant effect on employee loyalty, job satisfaction is a partially positive and significant effect on employee loyalty and organizational culture partially positive and significant effect on employee loyalty. And the results of hypothesis testing simultaneously the F calculated value is stated to be 41,570 and is included as greater than the F table 2.74. This means that Ho is rejected and Hi is accepted. And the significant value is 0.000 less than 0.05. So career development, job satisfaction, and organizational culture simultaneously have a significant effect on employee loyalty. Meanwhile, from the determination test, the R Square coefficient of 0.625 2 means that the relationship between career development, job satisfaction, and organizational culture on employee loyalty influences of 62.5%, while the remaining 37.5% is explained by other variables not included in the modeling.